Estimation of Intellectual Capital in the Sphere of Inclusive Education by the Example of University - B. Nadtochiy, Yu.; S. Budovich, L. (International Journal of Engineering and Technology, 2018)
The present article discusses the stages of a comprehensive assessment of the intellectual capital of a teacher in an educational organization in an inclusive education. The analysis of student survey data on the assessment of the teacher’s intellectual capital is presented. A comparison of the essence of concept and structure of intellectual capital in domestic and foreign scientific research has been carried out. Along with this, the authors propose and substantiate the criteria for evaluating the intellectual capital of an educational organization of higher education as a whole, based on the results of which it is possible to determine key areas for further development of the educational institution’s activities.